2011
DOI: 10.5897/ajb11.450
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and rooting of wild cherry: The influence of cytokinin and auxin types and their concentration

Abstract: Determination of the most optimal type and concentration of plant growth regulators as medium constituents is one of the most important aspects of successful micro propagation, among other in vitro factors. With the aim of optimization of in vitro multiplication of wild cherry, the effect of the following cytokinins was studied: 6-benzyladenine (BAP), 2-isopentenyl adenine (2iP) and kinetin (Kin) at concentrations of 1, 2, 4 and 8 mg. l-1. Stem segments of seedlings from juvenile and adult materials were disin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Although MS medium is still most widely used, it is often replaced by media of lower salt concentration, especially those with lower nitrogen content, including the content of ammonium nitrate which is 1650 mg•l -1 in MS medium and 1416 and 400 mg•l -1 in DKW and WPM, respectively. Most plants prefer nitrate to ammonium, and ammonium has been proved to be harmful for explants (Pierik 1997;Mansseri-Lamrioui et al 2011), because the excess of nitrate can be stored in vacuoles and high ammonium can be toxic (Glass et al 2002). On the other hand, DKW and WPM media have a higher calcium concentration compared to MS medium.…”
Section: Resultsmentioning
confidence: 99%
“…Although MS medium is still most widely used, it is often replaced by media of lower salt concentration, especially those with lower nitrogen content, including the content of ammonium nitrate which is 1650 mg•l -1 in MS medium and 1416 and 400 mg•l -1 in DKW and WPM, respectively. Most plants prefer nitrate to ammonium, and ammonium has been proved to be harmful for explants (Pierik 1997;Mansseri-Lamrioui et al 2011), because the excess of nitrate can be stored in vacuoles and high ammonium can be toxic (Glass et al 2002). On the other hand, DKW and WPM media have a higher calcium concentration compared to MS medium.…”
Section: Resultsmentioning
confidence: 99%
“…ex Godr (Marcu et al, 2014). The better effectiveness of IBA compared with NAA on rooting induction of A. occulta in this study could be attributed to several reasons including (1) more resistance to photodegradation, adherence to microshoots, and inactivation by biological action (Elmongi et al, 2018), (2) successive rooting gene activation, better uptake, transportation and stability (Liu et al, 2017), (3) slow migration and delayed degradation (Mansseri-Lamrioui et al, 2011), and (4) slower oxidization rate by the oxidase (Wolella, 2017) and thus of higher stability (Abbasi et al, 2019). It this study, the highest concentration (5 μM) of either IBA or NAA, and the simultaneous application of both auxins (IBA + NAA) irrespective their concentration combination ratios were detrimental and toxic resulting in complete rooting inhibition, which might be ascribed to ethylene synthesis induced due to high auxin concentrations (Aghaye and Yadollahi, 2012).…”
Section: In Vitro Rooting Under Different Auxin Types and Concentrationsmentioning
confidence: 73%
“…It has been shown that the majority of plants exhibit a preference for nitrate over ammonium as a source of nitrogen [66]. Previous studies have demonstrated that ammonium may have detrimental effects on explants [67,68]. This is attributed to the fact that excessive nitrate can be retained in vacuoles, whereas high levels of ammonium can be hazardous to plants.…”
Section: Evaluation Of the In Vitro Micropropagation Ability Of Black...mentioning
confidence: 99%